Estimation of Ultrasound Velocity Spatial Distributions in Green Ceramic Tiles - Kulokas, M.; Kazys, R.; Mazeika, L.; Sliteris, R.; Deksnys, V. (Elektronika ir Elektrotechnika, 2012)
From analysis of used and applicable quality control systems of ceramic tiles is clearly seen that the ultrasonic measurement systems have significant advantages. Each manufactured product in this case will be evaluated and the result will be obtained with a sufficient accuracy. Therefore, one of the applicable ultrasonic measurement systems for measurement of the density of ceramic tiles is analyzed in this article. In this case, ultrasound velocity measurements were performed in the sectors with a different thickness of the 0.105 m x 0.105 m size green ceramic tile using ultrasonic transducers developed in the Ultrasound Institute of Kaunas University of Technology with different acoustic contact zones. Such approach was necessary because the thickness of the tile in these zones is quite different. DOI: http://dx.doi.org/10.5755/j01.eee.18.9.2810